The First Clinic of Surgery in Lithuania and its Founders - Triponis, Vytautas; Triponienė, Dalia (Lietuvos chirurgija, 2022)
The developement of surgery in Vilnius and Lithuania is related to the Vilnius University Clinic of surgery founded in the middle of 1808–1809 academic year, that is more than 200 years ago and it was the first specialized clinical institution of the Grand Duchy of Lithuania. This new chapter at the Faculty of Medicine was orientated to the teaching and training of surgeons and developing their scientific approach to clinical practice. The Clinic of Surgery took over the concept of clinical education from the Clinic of Therapy which was initiated by Johan Peter Frank (1745–1821) and Joseph Frank (1771–1842) 3 years earlier. They were the founders of Vilnius medical Society as well. The concept consisted of the integration of basic theoretical knowledge into clinical skills learning. The basis of clinical training was ward round teaching on patient’s bedside, round the clock duty in the Clinic, continuous observation of patients and taking part in autopsy. Further developments of the Clinic were related to the activities of surgical professors from Western Europe, as well as highly experienced local doctors who immediately started lecturing and operating patients. These were the creators, developers and cherishers of the Clinic: Jacque Briotet (1746–1819), Johan Andreas Lobenwein (1758–1820), Johan Friedrich Niszkowski (1774–1816), Jakób Szymkiewicz (1775–1818), Konstantin Porcijanka (1793–1841). Foundation and successful operation of the surgical clinic signified a higher level in the evolution of Lithuanian clinical medicine. New concept of teaching and scientific approach to the diagnosis and surgical treatment made the clinic comparable to the European innovative medical institutions of the 19th century. The effective activities and future prospects were roughly cut off by Russian tsarist policy in 1832.